1977
DOI: 10.1159/000231955
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Total IgE and Cell-Mediated Immunity in Patients with Hodgkin’s Disease

Abstract: Thymus-derived lymphocytes have been shown to play a role in the regulation of IgE synthesis in the rat. Both anergy and elevated serum IgE levels may be present in patients with Hodgkin’s disease. Cell-mediated immunity (CMI) was investigated by measurement of delayed skin test reactions with five common antigens. Serum IgE levels were determined at the same time. Impaired CMI was more prevalent in patients in stage III (13 of 15) and IV (15 of 19), as compared to patients in stage I and II (9 of 17). All 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The current analyses support the earlier results in relation to B-cell lymphoma, but not HL, where we found a protective effect for both total and specific serum IgE. The majority of previous studies have reported an increased risk of HL with elevated IgE levels (15,16). Nonetheless, a recent large case-control study, using data from population based registries, reported asthma to be associated with a significantly decreased risk of HL (OR, 0.6; 95% CI, 0.4-0.9; based on 18 exposed cases), which is in accordance with our current results; after an induction period of 10 years after first asthma diagnosis, the OR was still below unity (OR, 0.7), but the result was no longer statistically significant (8).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current analyses support the earlier results in relation to B-cell lymphoma, but not HL, where we found a protective effect for both total and specific serum IgE. The majority of previous studies have reported an increased risk of HL with elevated IgE levels (15,16). Nonetheless, a recent large case-control study, using data from population based registries, reported asthma to be associated with a significantly decreased risk of HL (OR, 0.6; 95% CI, 0.4-0.9; based on 18 exposed cases), which is in accordance with our current results; after an induction period of 10 years after first asthma diagnosis, the OR was still below unity (OR, 0.7), but the result was no longer statistically significant (8).…”
Section: Discussionsupporting
confidence: 92%
“…Several large cohort linkage studies have reported no association with cancer risk and atopy or allergy (11,12). Elevated serum IgE levels have been reported in HL (13,14) and advanced stage of HL disease has also been found to correlate with elevated IgE (15). Eosinophilia, a hallmark of atopy, is also frequently observed among HL patients (16).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated IgE levels have been reported in Hodgkin's lymphoma (HL) and advanced stage of HL disease has also been found to be correlated with elevated IgE [78]. …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, many observations report high TE levels in those situations where at least some T-cell functions are reduced. In diseases such as Hodgkin's disease (30), Wiskott-Aldrich syndrome (31), and infectious mononucleosis (32) where Tcell function is suppressed and after T-suppressive manipulations such as thymectomy (33), irradiation (34), and treatment with antilymphocyte serum (35), TE production is enhanced. Indeed, a soluble factor apparently obtained from thymocytes has been isolated that can suppress TE responses (36).…”
Section: Discussionmentioning
confidence: 99%